PELATIHAN DAN PEMBUATAN WEBSITE MENGGUNAKAN HTML DAN CSS - Kumalasari, Intan; Saputra, Arif Azani; Pakpahan, Abram George Stephen; Kurtubi, Ahmad; Amiruddin, Abdullah; Fridaniarta, Bagas; Wicaksono, Erdo Yusuf; Saputra, Hasbi; Putra, Muhammad Yudha Arsya; Azahra, Rahma Yuni (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2023)
Web Design Making Training Using HTML And CSS at Nusantara Plus is a community service activity that aims to increase students' knowledge and understanding of creating a simple web. The training adopts a practical approach, wherein participants learn the fundamental steps of creating web pages with HTML and CSS. The learning methods include theoretical sessions, demonstrations, and hands-on practice to ensure optimal comprehension. The service activities that have been carried out are training on creating a simpleweb using VSCode, which can increase the knowledge and skills of Nusantara Pluss Middle School students. This training is carried out for one day by informatics engineering students at Pamulang University. The students directly practice on their respectivelab computers. Students reported increased knowledge of basic HTML structure, styling with CSS, and consistent design implementation